If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 2j + -7 Reorder the terms: 3 = -7 + 2j Solving 3 = -7 + 2j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-2j' to each side of the equation. 3 + -2j = -7 + 2j + -2j Combine like terms: 2j + -2j = 0 3 + -2j = -7 + 0 3 + -2j = -7 Add '-3' to each side of the equation. 3 + -3 + -2j = -7 + -3 Combine like terms: 3 + -3 = 0 0 + -2j = -7 + -3 -2j = -7 + -3 Combine like terms: -7 + -3 = -10 -2j = -10 Divide each side by '-2'. j = 5 Simplifying j = 5
| 5y+5=7y-7 | | -4x+3=21 | | 3(x-1)+2x=7 | | 4v+8=44 | | W-11=11 | | 12+5x=1+4x+3 | | -4+3=21 | | -2(-9+6x)=-18 | | -2y+24=30 | | 18=8+2h | | 31=3u+10 | | 5x^2+18x+-8=0 | | -133+10x=-7x+91 | | 23-c=21 | | -7x+8=-6x+9 | | -84=-7(p-2)-7p | | 49a^2-70a+25=0 | | -7x+4=22-4x | | 3(9+2x)=21 | | 7x+9-4x=15 | | y+9=6-2y | | 35-x-24= | | 3x-2+4-x=-4 | | 4d+3= | | 5m-2m-2=m-10 | | 6n-4=3n+11 | | 4x^2=-9+12x | | 2x-5=x+7-3x | | 6x+80+18x-40=180 | | 13-3n=1 | | 108=6-6(1-6x) | | 63=91-p |